2012
DOI: 10.1007/s10753-012-9471-4
|View full text |Cite
|
Sign up to set email alerts
|

HSF1 Is a Transcriptional Activator of IL-10 Gene Expression in RAW264.7 Macrophages

Abstract: The heat shock transcription factor (HSF) is an important transactivator of the heat shock genes. Recent studies have shown that HSF1 acts as a repressor of non-heat shock genes to protect against endotoxemia. In this study, we found that heat shock treatment and HSF1 over-expression augmented the induction of interleukin (IL)-10 mRNA. Computational analysis of the mouse IL-10 promoter region showed that three potential heat shock elements (HSEs) were located at mouse IL-10 gene promoter, among which only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…HSF1, an important heat shock transcription factor, is widely expressed in various types of cells and plays an important role in inflammation by regulating the transcription of inflammatory factors (2931). The acetylation of HSF1 decreases its DNA binding activity, and thus promotes the transcription of pro-inflammatory factors and inhibits the transcription of anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…HSF1, an important heat shock transcription factor, is widely expressed in various types of cells and plays an important role in inflammation by regulating the transcription of inflammatory factors (2931). The acetylation of HSF1 decreases its DNA binding activity, and thus promotes the transcription of pro-inflammatory factors and inhibits the transcription of anti-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-10 protein expression can be induced in response to activation of the heat shock response 22,23 . Thus, in the next series of experiments, we tested the hypothesis that prior activation of the heat shock response would exacerbate P. aeruginosa -induced lung injury and mortality via an IL-10-dependent mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…For example, previous work has shown that the initial response to the endogenous release or exogenous administration of anti-inflammatory mediators, such as IL-10, is associated with more severe lung injury caused by bacterial pneumonia 1321 . Furthermore, the heat shock factor 1 released during HSR activation is a transcriptional activator of the IL-10 gene expression in macrophages 22 and the fact that extracellular Hsp70 causes the release of IL-10 via the activation of the toll-like receptor-4 23 and enhances immunosuppressive function of CD4 + CD25 + FoxP3 + T regulatory cells that release IL-10 40 . In the present study, heat shocked alveolar macrophages released more IL-10 than cells kept at 37°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid organs harvested for transplantation may be stored at more extreme hypothermia for prolonged periods prior to transplant. Work from our group and others has shown that modest changes in temperature within the physiological range alters expression level of certain genes with important physiologic and clinical consequences (Cahill et al 1996;Chen et al 1997Chen et al , 2006Chen et al , 2009Wang et al 1998;Jiang et al 1999aJiang et al ,b, 2000Fairchild et al 2000;Singh et al 2000Singh et al , 2002Singh et al , 2008Hasday et al 2003;Ellis et al 2005;Appenheimer et al 2007;Vardam et al 2007;McClung et al 2008;Nagarsekar et al 2008Nagarsekar et al , 2012Cooper et al 2010a,b;Lipke et al 2010Lipke et al , 2011Fisher et al 2011;Maity et al 2011;Tulapurkar et al 2011Tulapurkar et al , 2012Zhang et al 2012;Gupta et al 2013). Most of the studies of temperature-dependent gene expression have focused on transcriptional regulation (Cahill et al 1996(Cahill et al , 1997Chen et al 1997;Singh et al 2008;Cooper et al 2010a,b;Maity et al 2011;Zhang et al 2012), but post-transcriptional regulation by small noncoding RNAs like microRNA (miRNA) may be as important as transcriptional regulation for ∼30% of all genes (Lewis et al 2005).…”
Section: Introductionmentioning
confidence: 99%